2006
DOI: 10.1111/j.1443-9573.2006.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of surgically induced acute liver failure by transplantation of HNF4‐overexpressing embryonic stem cells

Abstract: Transplantation of ES cells could be a potential treatment in supporting life during acute liver insufficiency and could be a bridge to orthotopic liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Consistent with previous reports [Ishizaka et al, ; Kanda et al, ], when cells were cultured in induction media containing some inducing factors, Foxa2 expression significantly increased differentiation into hepatocyte‐like cells. Although the stable constitutive expression of Foxa2 and Hnf4a increased differentiation to a less significant level compared with that of Foxa2 alone, Hnf4a expression alone could not increase differentiation, a result that is inconsistent with a previous report [Kuai et al, ]. Our results were confirmed by quantitative PCR, immunofluorescence, FACS analysis and PAS staining.…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with previous reports [Ishizaka et al, ; Kanda et al, ], when cells were cultured in induction media containing some inducing factors, Foxa2 expression significantly increased differentiation into hepatocyte‐like cells. Although the stable constitutive expression of Foxa2 and Hnf4a increased differentiation to a less significant level compared with that of Foxa2 alone, Hnf4a expression alone could not increase differentiation, a result that is inconsistent with a previous report [Kuai et al, ]. Our results were confirmed by quantitative PCR, immunofluorescence, FACS analysis and PAS staining.…”
Section: Discussionmentioning
confidence: 93%
“…Following transplantation, engrafted cells are exposed to various combinations of cytokine/growth factor signals in their own local microenvironment and experience direct cellular interactions with adjacent host tissue. Results from recent studies suggest that local microenvironmental cues from the host tissue encompassing the transplanted cells influence the ability of the grafted cells to differentiate(25; 34; 47). This has led to the concept that organ-specific cytokine/growth factors can direct ES cells into organ-specific cell-type differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the concept that organ-specific cytokine/growth factors can direct ES cells into organ-specific cell-type differentiation. For example, undifferentiated ES cells (1×10 5 cells) transplanted into the CCl4 treated mice will differentiate into hepatic cells when they are exposed to local liver-specific cytokines/growth factors with no evidence of teratoma formation(25; 34; 47). Based on this concept of tissue-specific microenvironments, many investigators have transplanted undifferentiated ES cells into different organs and observed tissue-specific differentiation without teratoma formation (25; 34; 47).…”
Section: Introductionmentioning
confidence: 99%
“…The basic role of Hnf4a in liver development has been previously demonstrated. In addition, it could induce a hepatic program in ES cells [30]. Therefore we choose Hnf4a factor for analysis of hepatic gene expression upon its overexpression in two differentiation methods.…”
Section: Discussionmentioning
confidence: 99%